Pendidikan Karakter Profil Pelajar Pancasila Melalui Wirid Remaja - Sari, Diska; Fidra, Afifah Salsabillah; Irman, Irman; Susanti, Elva; Siska, Leni; Desi, Desi (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2024)
Adolescence is a transition period between childhood and adulthood, during which time they are looking for their identity and therefore need the right assistance. One thing that is done is to develop the character profile of Pancasila students with teenage wirid. This teenage wirid is not only for reciting the Koran but also for carrying out religious activities, both obligatory and sunnah. The method used is community education, namely counseling to educate teenagers and provide understanding to develop the character profile of Pancasila students.